The Adoption of Augmented Reality (AR) Advertising in Malaysia: A Foresight Perspective - Nurul Balqis Mohd Hairudin; WAHAB, ETA (Research in Management of Technology and Business, 2024)
Augmented reality (AR) advertising is the new method of marketing tools which focuses on the fact that able to change dramatically the way any brand communicates and interact with users in realistic way and help users to obtain good experience of the real product. Nevertheless, there is a dearth of study on the use of augmented reality advertising in Malaysia.. Thus, the purpose of this study is to identify the key drivers of Augmented Reality (AR) advertising adoption and to determine the future trend of Augmented Reality (AR) advertising adoption among consumers in Malaysia. STEEPV analysis was used to determine the key drivers or issues of Augmented Reality (AR) advertising adoption among consumers in Malaysia. The analysis of STEEPV shows that technological factor is the most important driver in augmented reality advertising followed by values, economics, social, political, and environmental factor. 11 merged key drivers and issues had been found. The impact uncertainty analysis method was employed to determine the augmented reality advertising trend that Malaysia might faced in the future. A total of 384 questionnaires were distributed to advertising company in Malaysia with response rate of 30.2%. The study found that privacy policies protection and AR technology interaction between virtual world and real life have the highest impact and the highest uncertainty. Four scenarios were proposed at the end of the study., low/sluggish capability, deficiency of technology and vulnerability.